1975
DOI: 10.1111/j.1749-6632.1975.tb29278.x
|View full text |Cite
|
Sign up to set email alerts
|

REDUCTION OF GASTRTC CARCINOGENS WITH ASCORBIC ACID*

Abstract: The formation of nitrite from nitrate was studied in potatoes incubated at room temperature. After 24 hours of incubation at 25 degrees, 112 ppm and 373 ppm of nitrite formed in homogenized cooked potatoes containing 284 ppm and 584 ppm of nitrate, respectively. In homogenized fresh potatoes incubated at 21 degrees and containing 284 ppm of nitrate, 103 ppm of nitrate formed within 24 hours. During the period of nitrite formation, nitrate levels decreased sharply, indicating that reduction of nitrate to nitrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

1978
1978
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(14 citation statements)
references
References 13 publications
0
13
0
1
Order By: Relevance
“…Green and yellow vegetables are very rich in vitamin C, and has been found to be protective against stomach cancer in a number of experimental and epidemiological studies. Thus, vitamin C may inhibit gastric cancer cell growth, be a possible means of blocking the formation of human carcinogenic N-Nitroso compounds, and may reduce nitrite concentration by 43% (Mirvish et al, 1972;Raineri and Weisburger, 1975;Zhang et al, 2002). A prospective cohort study found a significantly decreased risk of progression to dysplasia or gastric cancer among subjects with high blood ascorbic acid level (OR=0.2, 95% CI=0.1 -0.7) (You et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Green and yellow vegetables are very rich in vitamin C, and has been found to be protective against stomach cancer in a number of experimental and epidemiological studies. Thus, vitamin C may inhibit gastric cancer cell growth, be a possible means of blocking the formation of human carcinogenic N-Nitroso compounds, and may reduce nitrite concentration by 43% (Mirvish et al, 1972;Raineri and Weisburger, 1975;Zhang et al, 2002). A prospective cohort study found a significantly decreased risk of progression to dysplasia or gastric cancer among subjects with high blood ascorbic acid level (OR=0.2, 95% CI=0.1 -0.7) (You et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Results from previous studies suggested that a diet rich in vitamin C was protective, whereas a diet high in salt might increase the risk of stomach cancer (Mirvish et al, 1972;Raineri and Weisburger, 1975;Joossens et al, 1996;Zhang et al, 2002). Sources of vitamin C include fresh foods, such as green and yellow vegetables, fruit and other fresh foods, while salt ingestion is from processed, pickled, preserved, salted foods, and also seasoning (Kagawa, 1991).…”
mentioning
confidence: 99%
“…Oranges and tangerines are a rich source of vitamin C in the diet. It is known that vitamin C can block nitrosamine formation in vivo (Raineri and Weisburger, 1975), thereby offering a biological rationale for the observed protective effect of oranges/tangerines in NPC development. In a case-control study, Farrow et al (1998) reported that high intake of vitamin C was associated with a significant, dose-dependent reduction in risk of NPC among US blacks and whites.…”
Section: Discussionmentioning
confidence: 99%
“…Seventh-Day Adventists have a restricted fat and meat intake when compared to other populations living in the same district and, as indicated, they suffer considerably less often from breast and colon cancer. 28 Some researchers have postulated that a low fiber intake in western countries may be responsible for a high incidence in colon cancer. Indeed the Japanese diet is high in fiber content, as is the diet of African populations.…”
Section: Vol I Nomentioning
confidence: 99%